Nghiên cứu chế tạo bạc nano bằng phương pháp chiếu xạ gamma Co-60 sử dụng alignat làm chất ổn định - Loan, Nguyễn Thị Kim; Phú, Đặng Văn; Lăng, Võ Thị Kim; Duy, Nguyễn Ngọc; Hạnh, Trương Thị; Anh, Nguyễn Tuệ; Hiến, Nguyễn Quốc (Vietnam Journal of Chemistry, 2012)
Silver nanoparticles have been widely applied in many fields. In this study, silver nanoparticles were prepared by gamma Co-60 irradiation using alginate as stabilizer. The conversion dose (Ag+® Ag0) was determined by UV-vis spectroscopy and the average size of silver nanoparticles was characterized by transmission electron microscopy (TEM). As a result, the particle sizes were in the range of  6 - 12 nm for Ag+ concentration from 1 to 5 mM. The effect of alginate concentration and the stability of colloidal silver nanoparicles solution were also investigated.